Biomass composite nano antibacterial agent, flexible antibacterial plastic and preparation method thereof
By modifying nano zinc oxide and combining it with biomass-based powder, biomass composite nanoantibacterial agents are prepared, which solves the problem that antibacterial agents in existing antibacterial plastics affect the performance of plastics, and achieves efficient and safe antibacterial effects.
Patent Information
- Application Number
- CN202310414708.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-18
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-04-18
AI Technical Summary
When using nano-oxidized metal antibacterial agents, existing antibacterial plastics are prone to affect the hydrophilic and mechanical properties of the plastic, and the antibacterial properties of pure nano-oxidized metals are poor.
By modifying nano zinc oxide, combining biomass-based powder such as hemp stalk core powder, biomass composite nanoantibacterial agent is prepared and added to plastic to improve antibacterial properties while maintaining or improving the mechanical and waterproof properties of the plastic.
Antibacterial plastics with non-toxic and excellent antibacterial properties are achieved, avoiding the problem of degradation of mechanical properties and waterproofness after the addition of antibacterial agents, and have good applicability and cost advantages.
Smart Images

Figure CN116355431B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of antibacterial materials, and specifically relates to a biomass composite nano antibacterial agent, a flexible antibacterial plastic containing the antibacterial agent, and a preparation method of the two. Background Art
[0002] With the improvement of living standards and technological standards, people's requirements for their own environmental hygiene and safety have also increased significantly. As the most common daily necessities that people come into contact with in daily life, the antibacterial properties of plastic products have attracted much attention, and the requirements for the antibacterial and mildew-proof effects of raw materials have become more stringent. The demand for the research and development of antibacterial agents suitable for the dip molding method is also more urgent. The dip molding method is called the metal dip coating method. It is a common method for preparing plastic products by heating the metal mold to attract plastic particles in the thermal motion process to adsorb on the surface of the metal mold, and then high-temperature curing and molding. Therefore, the dip molding method has high requirements for the thermal stability of the material itself.
[0003] In recent years, nano-metal oxide antibacterial agents have been widely used in the field of antibacterial agents due to their non-toxicity and excellent stability. However, pure nano-metal oxide has poor antibacterial properties and is prone to water absorption, which limits its scope and conditions of use. Especially when used in plastics, it is easy to affect the waterproof and mechanical properties of plastic products.
[0004] Prior art: Chinese patent CN110857356B provides an antibacterial plastic and a method for preparing the same. The antibacterial agent is a composite nano antibacterial agent, and plant extracts and nano sterile antibacterial powders are used in the composite nano antibacterial agent. The antibacterial plastic is claimed to be able to fundamentally reduce plastic toxicity and improve the safety of plastic use while ensuring antibacterial properties. However, zinc oxide and titanium oxide powders are used in the composite nano antibacterial agent, and the hydrophilic groups introduced by the use of the two have a greater impact on the hydrophilic and hydrophobic properties of the plastic body. Chinese patent CN115594908A provides an antibacterial plastic and a method for preparing the same. The components mainly include a plastic base material and a nano antibacterial agent dispersed therein. The antibacterial agent improves the binding ability of the two and the compatibility of the plastic base material by modifying silicon dioxide and compounding with photocatalytically active nanoparticles, and enables the plastic to obtain good intrinsic antibacterial and light-mediated antibacterial effects, achieving good long-term antibacterial properties and biosafety. However, although the above particles can improve the good antibacterial effect, their hydrophilic properties are not solved. The addition of the particles will inevitably affect the hydrophilic and hydrophobic properties of the plastic, and the effect of the addition of particles on the mechanical properties of the plastic is not explored. The above factors will become important factors affecting the practical application of antibacterial plastics. Chinese patent CN114634679A provides an antibacterial plastic and a preparation method thereof. The composition of the antibacterial agent mainly includes zinc oxide, titanium oxide and graphene particles, and the obtained antibacterial agent is added to the mixed plasticizing and curing reaction of the plastic to mix and prepare the antibacterial plastic, and it is claimed that the obtained antibacterial plastic has strong heat resistance and good antibacterial properties; but although the composite of graphene and metal oxide particles can effectively improve its photocatalytic antibacterial properties, and graphene can help provide good heat resistance, the compounding of the above three hydrophilic substances aggravates the influence on the hydrophilicity of the plastic system, and the corresponding technical problems have not been solved. Summary of the invention
[0005] In view of the above problems, the present invention provides a biomass composite nano antibacterial agent, a flexible antibacterial plastic and a preparation method thereof. By modifying nano zinc oxide, while improving its photocatalytic antibacterial effect, the hydrophilic and hydrophobic properties of nano zinc oxide can be effectively improved, thereby avoiding the phenomenon of a significant impact on the hydrophilic and hydrophobic properties of the antibacterial plastic.
[0006] In order to solve the above problems, the present application is implemented through the following technical solutions:
[0007] A biomass composite nano antibacterial agent, the raw materials of which include, by weight, 0.1-5 parts of nano metal oxide, 0.1-5 parts of biomass base powder and 15-50 parts of solvent.
[0008] As a preferred solution, the nano metal oxide is at least one of nano zinc oxide, nano antimony oxide, nano titanium oxide, modified nano zinc oxide, modified nano antimony oxide and modified nano titanium oxide, more preferably modified nano zinc oxide.
[0009] As a preferred solution, the modified nano zinc oxide is prepared by the following steps:
[0010] (1) Dissolve succinic anhydride in DMF (N, N-dimethylformamide), add a certain amount of (3-aminopropyl)triethoxysilane, and stir at 60-80°C (water bath temperature) for 1-2 hours;
[0011] (2) adding a certain amount of zinc oxide DMF solution to the reaction solution in step (1), stirring and reacting for 2-3 hours, separating and drying to obtain pretreated zinc oxide particles;
[0012] (3) The obtained pretreated zinc oxide particles are mixed with a certain amount of 2-methylimidazole and zinc nitrate, and then a portion of the mixture is added to toluene, and the mixture is slowly stirred at 60-80°C for a pre-reaction of 30-40 minutes. After a small amount of white flocculent precipitates, the remaining mixture is added, and the reaction is continued for 4.5-5 hours. The mixture is filtered and dried to obtain the product.
[0013] As a preferred solution, the mass ratio of succinic anhydride, (3-aminopropyl)triethoxysilane and zinc oxide is (2.5-3.5):(1.6-2.4):1.
[0014] As a preferred solution, the mass ratio of the pretreated zinc oxide particles to 2-methylimidazole and zinc nitrate is 0.5-1:10-15:3-5.
[0015] In the technical solution of the present application, by composite modification of zinc oxide, and controlling the modification conditions and the average particle size of the final modified particles, the negative impact of the addition of zinc oxide particles on the mechanical properties and waterproof properties of plastic products in the prior art can be avoided on the basis of further improving the antibacterial properties of antibacterial plastics. The modified zinc oxide can be uniformly loaded on the skeleton material formed by stacking by bonding, and form a large-area heterojunction photocatalytic structure, which greatly reduces the electron-hole recombination rate and the forbidden band distance in the above-formed structure, thereby greatly improving the antibacterial properties of the zinc oxide particles themselves; on the other hand, the formed skeleton carrier can "neutralize" the hydrophilic groups on the surface-loaded zinc oxide particles through its exposed hydrophobic surface, thereby achieving the hydrophobic properties of the overall composite particles.
[0016] As a preferred solution, the biomass-based powder is at least one of hemp stalk core powder, peanut shell powder and rice husk powder, more preferably hemp stalk core powder.
[0017] As a preferred solution, the average particle size of the biomass-based powder is 1000-3000 mesh, more preferably 1800-2000 mesh.
[0018] As a preferred solution, the mass ratio of the nano metal oxide to the biomass-based powder is (1-3):(1-3), more preferably 1:1.
[0019] As a preferred solution, the solvent is an organic alcohol, more preferably a mixture of isopropanol, butanol and tert-butyl alcohol, the mass ratio of the three being (2-3):(0.5-1):(0.5-1), which is 2.5:0.8:0.8.
[0020] The present invention provides a preparation method of the above-mentioned biomass composite nano antibacterial agent, comprising the following steps: mixing nano metal oxide and biomass base powder in proportion, adding them to a solvent, and obtaining a suspension after ultrasonic dispersion; mechanically stirring the suspension at a stirring speed of 600-800 r / min and a stirring time of 0.5-3h, and centrifuging and drying after the stirring is completed to obtain the biomass composite nano antibacterial agent.
[0021] The present invention also provides a flexible antibacterial plastic, the raw materials of which include at least the above-mentioned biomass composite nano antibacterial agent and plastic resin dipping solution; the mass ratio of the biomass composite nano antibacterial agent to the plastic resin dipping solution is (0.1-5): (80-120), more preferably (0.6-3):100.
[0022] As a preferred solution, the plastic resin in the plastic resin dipping solution is at least one of PVC (polyvinyl chloride), PET (polyethylene terephthalate), PC (polycarbonate), PP (polypropylene), PE (polyethylene), PVA (polyvinyl alcohol) and ABS (acrylonitrile-butadiene-styrene copolymer).
[0023] As a preferred solution, the plastic resin dipping solution comprises, by weight, 80 to 120 parts of PVC powder, 60 to 100 parts of plasticizer, 1 to 3 parts of stabilizer, 1 to 5 parts of pigment, and 1 to 3 parts of filler.
[0024] As a preferred solution, the plasticizer is at least one of dioctyl terephthalate DOTP, dioctyl phthalate DOP, epoxidized soybean oil ESO, and diisononyl phthalate DINP.
[0025] As a preferred solution, the stabilizer is at least one of a calcium zinc stabilizer, an organic tin stabilizer, and a barium zinc stabilizer.
[0026] As a preferred solution, the filler is at least one of calcium carbonate, barium sulfate, talcum powder, ceramic powder, white carbon black, aluminum hydroxide, magnesium oxide, and bentonite.
[0027] As a preferred solution, the pigment is at least one of titanium dioxide, iron oxide red, iron oxide yellow, carbon black and phthalocyanine blue. Beneficial Effects
[0028] 1. The antibacterial plastic of the present invention is non-toxic and has excellent antibacterial properties. It can also avoid the phenomenon of decreased mechanical properties and decreased waterproofness due to the addition of antibacterial agents, and has very excellent applicability.
[0029] 2. The antibacterial plastic of the present invention, the hemp stalk core powder in the antibacterial agent used not only contains a large amount of phenols that can inhibit and kill mold microorganisms, but also has a peculiar rough and porous surface, which allows air to enter more easily, thereby inhibiting the growth of anaerobic bacteria, and the rough and porous surface of hemp is also conducive to the loading and dispersion of modified zinc oxide, thereby obtaining more excellent antibacterial performance and safety; on the other hand, the hemp stalk core powder used is inexpensive, healthy and safe, and has excellent cost advantages.
[0030] 3. The antibacterial agent used in the antibacterial plastic of the present invention releases antibacterial molecules that can affect the structure of bacterial cell membranes. When these ions come into contact with sites on the bacterial cell membrane, they destroy the transfer function of the cell membrane, causing functional disorders, and then enter the cell and combine with proteins, affecting DNA synthesis, and ultimately restricting bacterial growth and reproduction. In addition, the rough and porous surface structure on the hemp stalk core powder can effectively play the role of slow-release zinc oxide composite particles, thereby extending the antibacterial timeliness of the overall plastic.
[0031] 4. In the antibacterial plastic of the present invention, the antibacterial agent used improves the antibacterial, mechanical and hydrophobic properties of the plastic product by composite modification of zinc oxide particles and controlling the modification conditions and the average particle size of the final modified particles. This is because the modified zinc oxide can be uniformly loaded on the skeleton material formed by stacking through bonding, and form a large-area heterojunction photocatalytic structure, which can greatly reduce the electron-hole recombination rate in the above-formed structure and reduce the bandgap distance, thereby greatly improving the antibacterial properties of the zinc oxide particles themselves; on the other hand, the formed skeleton carrier can "neutralize" the hydrophilic groups on the surface-loaded zinc oxide particles through its exposed hydrophobic surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1The figures are graphs showing the antibacterial test results of the flexible antibacterial plastic prepared by the present invention; in the figure, A shows the antibacterial effect of PVC without adding an antibacterial agent (blank control), B shows the antibacterial effect of PVC with 0.6% of the composite nano antibacterial agent (Example 1), C shows the antibacterial effect of PVC with 1.0% of the composite nano antibacterial agent (Example 2), D shows the antibacterial effect of PVC with 1.5% of the composite nano antibacterial agent (Example 3), and E shows the antibacterial effect of PVC with 2.0% of the composite nano antibacterial agent (Example 4).
[0033] Figure 2 The figure is a graph showing the antibacterial test results after adding the composite nano antibacterial agent of the present invention to plastics using Staphylococcus aureus as the experimental strain; in the figure, A is the antibacterial effect of L-11 without adding antibacterial agent (blank control), B is the antibacterial effect of L-11 with 1.0% composite nano antibacterial agent (Example 5), C is the antibacterial effect of L-11 with 2.0% composite nano antibacterial agent (Example 6), and D is the antibacterial effect of L-11 with 3.0% composite nano antibacterial agent (Example 7).
[0034] Figure 3 The SEM electron microscope images of the flexible antibacterial plastic of the present invention; a is a SEM photo of a cross section of ordinary PVC (blank control), b is a SEM photo of a cross section of an antibacterial PVC with an antibacterial agent content of 1.0% (Example 2), and c is a SEM photo of the surface of an antibacterial PVC with an antibacterial agent content of 1.5% (Example 3).
[0035] Figure 4 It is a tensile property test diagram of common PVC plastic (blank control) and Examples 1, 2, 3 and 4 of the present invention.
[0036] Figure 5 4 is a comparison chart of the tensile properties of the embodiments of the present invention (embodiments 5, 6, and 7).
[0037] Figure 6 4 is a comparison chart of the tear strength performance of the embodiments of the present invention (embodiments 5, 6, and 7).
[0038] Figure 7 4 is a comparison chart of the hardness performance of the embodiments of the present invention (embodiments 5, 6, and 7).
[0039] Figure 8 Table showing the test results of antibacterial performance and water contact angle. Implementation
[0040] Example
[0041] A biomass composite nano antibacterial agent, whose raw materials include, by weight, 0.3 parts of nano metal oxide, 0.3 parts of biomass base powder and 15 parts of solvent.
[0042] The nano metal oxide is nano zinc oxide, and has undergone composite modification. The modification steps include: (by mass) (1) dissolving 3 parts of succinic anhydride in 50 parts of DMF solution, adding 2 parts of (3-aminopropyl) triethoxysilane, heating and stirring at a water bath temperature of 70°C for 1.5 hours; (2) then dropping a DMF solution containing 1 part of zinc oxide into the reaction solution, stirring and reacting for 2.5 hours to obtain 1 part of pretreated zinc oxide particles; (3) mixing 1 part of pretreated zinc oxide particles with 11 parts of 2-methylimidazole and 3.5 parts of zinc nitrate, and preferentially adding 10wt% of the raw materials of the mixture to 100 parts of toluene solvent, slowly stirring and pre-reacting at 65°C for 30 minutes, and after a small amount of white flocculent precipitates, adding the remaining raw materials, continuing the reaction for 4.5 hours, filtering and drying to obtain the obtained composite modified nano zinc oxide. The average particle size of the obtained composite modified nano zinc oxide is 480nm.
[0043] The biomass-based powder is hemp stalk core powder, and its average particle size is 2000 mesh. The hemp stalk core powder is purchased from Guangdong Hanma Biotechnology Co., Ltd.
[0044] The solvent is a mixture of isopropanol, butanol and tert-butyl alcohol, and the mass ratio of the three is 2.5:0.8:0.8.
[0045] This embodiment also provides a method for preparing the above-mentioned biomass composite nano antibacterial agent, which comprises the following steps: (1) mixing nano metal oxide and biomass base powder in proportion, adding them to a solvent, and obtaining a suspension after ultrasonic dispersion; (2) mechanically stirring the suspension at a stirring speed of 800 r / min and a stirring time of 2.5 h. After the stirring is completed, centrifuging and drying the suspension to obtain the antibacterial agent.
[0046] The third aspect of this embodiment provides a flexible antibacterial plastic, the raw materials of which include the above-mentioned biomass composite nano antibacterial agent and plastic resin dipping liquid.
[0047] The mass ratio of the biomass composite nano antibacterial agent to the plastic resin dipping solution is 0.6:100.
[0048] The plastic resin dipping liquid is PVC dipping liquid. The raw materials of the PVC dipping liquid, calculated by mass, include: 100 parts of PVC powder, 90 parts of plasticizer, 1.5 parts of stabilizer, 2 parts of pigment and 1.5 parts of filler.
[0049] The PVC powder is KM-31. The filler is calcium carbonate; the pigment is titanium dioxide; the plasticizer is dioctyl terephthalate DOTP; and the stabilizer is calcium zinc stabilizer, which were purchased from Aidico Fine Chemicals (Shanghai) Co., Ltd. Example
[0050] The specific implementation of this embodiment is the same as that of Embodiment 1, except that: the raw materials of the antibacterial plastic, in parts by mass, include: 0.5 parts of nano metal oxide, 0.5 parts of biomass-based powder, 20 parts of solvent and 100 parts of plastic resin dipping solution.
[0051] The amount of antimicrobial agent added to the plastic (by mass percentage) is 1%. Example
[0052] The specific implementation of this embodiment is the same as that of Embodiment 1, except that: the raw materials of the antibacterial plastic, in parts by mass, include: 0.75 parts of nano metal oxide, 0.75 parts of biomass-based powder, 30 parts of solvent and 100 parts of plastic resin dipping solution.
[0053] The amount of antimicrobial agent added to the plastic (by mass percentage) is 1.5%. Example
[0054] The specific implementation of this embodiment is the same as that of Embodiment 1, except that: the raw materials of the antibacterial plastic, in parts by mass, include: 1 part of nano metal oxide, 1 part of biomass base powder, 40 parts of solvent and 100 parts of plastic resin dipping solution.
[0055] The amount of antimicrobial agent added to the plastic (by mass percentage) is 2%. Example
[0056] The specific implementation of this embodiment is the same as that of Embodiment 1, except that: the raw materials of the antibacterial plastic, in parts by mass, include: 0.5 parts of nano metal oxide, 0.5 parts of biomass-based powder, 60 parts of solvent and 100 parts of plastic resin dipping solution.
[0057] The plastic resin dipping liquid is PVC dipping liquid. The raw materials of the PVC dipping liquid, calculated by mass, include: 100 parts of PVC powder, 90 parts of plasticizer, 1.5 parts of stabilizer, 2 parts of pigment and 1.5 parts of filler.
[0058] The PVC powder was PSH-10 purchased from Shenyang Chemical. The filler was calcium carbonate; the pigment was titanium dioxide; the plasticizer was dioctyl terephthalate DOTP; and the stabilizer was calcium zinc stabilizer purchased from Aidico Fine Chemicals (Shanghai) Co., Ltd.
[0059] The amount of antimicrobial agent added to the plastic (by mass percentage) is 1%. Example
[0060] The specific implementation of this embodiment is the same as that of Embodiment 5, except that: the raw materials of the antibacterial plastic, in parts by mass, include: 1 part of nano metal oxide, 1 part of biomass base powder, 40 parts of solvent and 100 parts of plastic resin dipping solution.
[0061] The amount of antimicrobial agent added to the plastic (by mass percentage) is 2%. Example
[0062] The specific implementation of this embodiment is the same as that of Embodiment 5, except that: the raw materials of the antibacterial plastic, in parts by mass, include: 1.5 parts of nano metal oxide, 1.5 parts of biomass base powder, 60 parts of solvent and 100 parts of plastic resin dipping solution.
[0063] The amount of antimicrobial agent added to the plastic (by mass percentage) is 3%. Example
[0064] The specific implementation of this embodiment is the same as that of Embodiment 6, except that: the preparation method of the antibacterial plastic comprises the following steps: in step (2), the suspension is mechanically stirred at a speed of 400 r / min for a stirring time of 0.5 h. Example
[0065] The specific implementation of this embodiment is the same as that of Embodiment 5, except that: 1.6 parts of nano metal oxide and 0.4 parts of biomass-based powder. Example
[0066] The specific implementation of this embodiment is the same as that of Embodiment 5, except that: 0.4 parts of nano metal oxide and 1.6 parts of biomass-based powder. Example
[0067] The specific implementation of this embodiment is the same as that of Embodiment 5, except that in the antibacterial agent raw material, the zinc oxide particles are ordinary nano zinc oxide with an average particle size of 25 nm.
[0068] The test and evaluation results of the antibacterial properties and water contact angle of the flexible antibacterial plastics obtained in Examples 1 to 11 are as follows: Figure 8 shown.
[0069] Antibacterial performance: The antibacterial performance of the samples prepared in all embodiments was tested, referring to GB / T 21510-2008, and the antibacterial performance of antibacterial PVC was tested by the film sticking method. Ten samples were tested in each embodiment, and the average value of the measured values was recorded. The results are shown in Figure 8 shown.
[0070] Water contact angle test: Samples prepared in all embodiments were prepared, and the sample specifications were 2mm x 2mm x2mm. The water contact angle on the sample surface was tested using the sessile drop method. The test time limit was 5s, and the test water droplet was 2 microliters. Ten samples were tested for each comparative example, and the average value of the measured values was recorded. Figure 8 .
[0071] Antibacterial PVC scanning electron microscopy: The blank control and the samples prepared in Examples 2 and 3 were subjected to scanning electron microscopy characterization and analysis of antibacterial PVC. In order to study the effect of the internal structure morphology of the antibacterial PVC composite material on the mechanical properties, PVC samples of appropriate size were frozen and brittle fractured in liquid nitrogen to obtain a flat cross section; the brittle fracture samples were gold-plated in vacuum, and the internal structure of the PVC samples (blank control and Examples 2 and 3) was observed under a scanning electron microscope (EVO 18, Germany). The results are shown in FIG. Figure 3 shown.
[0072] Mechanical properties: With reference to GB / T 1040.3-2006, the tensile strength and elongation at break of the samples prepared in the examples were tested for tensile properties (Examples 1, 2, 4, 5, 6, 7), and the tear strength and hardness of the samples prepared in the examples were tested (Examples 5, 6, 7). The test results are as follows: Figures 4 to 7 shown.
Claims
1. A flexible antibacterial plastic, characterized in that: The raw materials at least include a biomass composite nano antibacterial agent and a plastic resin dipping solution; the mass ratio of the biomass composite nano antibacterial agent to the plastic resin dipping solution is (1-3): 100; The plastic resin in the plastic resin dipping solution is polyvinyl chloride; The raw materials of the biomass composite nano antibacterial agent include, by weight, 0.1-5 parts of nano metal oxide, 0.1-5 parts of biomass base powder and 15-50 parts of solvent; The nano metal oxide is modified nano zinc oxide; The modified nano zinc oxide is prepared by the following steps: (1) Dissolve succinic anhydride in N, N-dimethylformamide, add a certain amount of (3-aminopropyl)triethoxysilane, and stir at 60-80°C for 1-2 hours; (2) adding a certain amount of zinc oxide DMF solution to the reaction solution in step (1), stirring and reacting for 2-3 hours, separating and drying to obtain pretreated zinc oxide particles; (3) Mix the obtained pretreated zinc oxide particles with a certain amount of 2-methylimidazole and zinc nitrate, then add a portion of the mixture into toluene, slowly stir and pre-react at 60-80°C for 30-40 minutes, and after white flocculent precipitates are formed, add the remaining mixture, continue to react for 4.5-5 hours, filter and dry to obtain the product; The mass ratio of succinic anhydride, (3-aminopropyl)triethoxysilane and zinc oxide is (2.5-3.5): (1.6-2.4): 1; The mass ratio of the pretreated zinc oxide particles to 2-methylimidazole and zinc nitrate is 0.5-1:10-15:3-5; The biomass-based powder is hemp stalk core powder; the average particle size of the biomass-based powder is 1000-3000 mesh; The mass ratio of the nano metal oxide to the biomass-based powder is (1-3): (1-3); the solvent is a mixture of isopropanol, butanol, and tert-butyl alcohol, and the mass ratio of the three is (2-3): (0.5-1): (0.5-1); The preparation method of the biomass composite nano antibacterial agent comprises the following steps: mixing nano metal oxide and biomass base powder in proportion, adding the mixture into a solvent, and obtaining a suspension after ultrasonic dispersion; mechanically stirring the suspension at a stirring speed of 600-800 r / min and a stirring time of 0.5-3 h, and centrifuging and drying the suspension after the stirring is completed to obtain the biomass composite nano antibacterial agent.
Citation Information
Patent Citations
An antibacterial plastic for automotive interior parts and its preparation method
CN110857356B
Preparation method of antibacterial plastic
CN114634679A
Antibacterial plastic and preparation method thereof
CN115594908A
Environment-friendly PVC plastic dipping liquid
CN108102245A
Heat-conducting adhesive film for solar cell and application of heat-conducting adhesive film
CN114716919A